Cash Management Strategies and Profitability: Evidence from MSME Retail Fashion Liga Store ID Makassar - Sulfiana; A. Anniza Putri Aulia; Hasrina; Kiki (www.amertainstitute.com, 2025)
Unstable cash flows remain a critical constraint on growth and earnings in many micro, small, and medium enterprises (MSMEs), especially in fast moving retail segments. This study examines how cash management strategies shape profitability performance in Liga Store ID Makassar, an MSME retail fashion business in Indonesia. The study objectives are to (1) identify the enterprise’s cash management practices, (2) analyze how those practices support liquidity discipline, and (3) interpret their relationship with profitability indicators. A qualitative descriptive design was used. Purposive sampling targeted key financial actors (owner and administrative finance staff). Data were obtained through in depth, semi structured interviews and corroborated with internal financial documents (cash logs, expense records, profit reports). Descriptive references to Return on Assets (ROA) and Return on Equity (ROE) informed interpretation of profitability tendencies. Results indicate that Liga Store ID applies an integrated, low cost cash control bundle: strict petty cash limits, daily Excel based transaction recording, routine monthly cash flow planning, early payment discount capture from suppliers, and spending caps linked to projected inflows. These practices help preserve liquidity, reduce leakage, and support margin improvement—as reflected in observed movements in profitability ratios across review periods. Ongoing constraints include limited digital accounting capability, uneven financial literacy, and customer payment timing gaps that sustain cash flow volatility. The study extends MSME finance literature by demonstrating that context appropriate cash management bundles can reinforce financial resilience and profitability in small retail enterprises, and offers practical guidance for upgrading cash budgeting discipline and digital recordkeeping in similar settings.